(3cJGH eSGMI GdCTcGd GdHSjWI hGdcQjIs - ((3Hfj ehSi (B( (3eMeO hGdMSf hCMeOs
(3ChdgG (B:s
(3GdWhd Cbd GdCbOGQ GdJi GdCTcGd hgh eG GeJO Ydi GSJbGeI ai GdNeS LejYkG aEfg dGjchf efg GdC(B"(3hGd abW s
(3BNQgG (B:s
(3hjchf cPdc VQH eQHY O W ai eQHY g` M hPdc eG CQOfGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS YTQs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1458s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs